Shape transitions and collective behaviour of Er and Yb isotopes based on relativistic energy density functional theory - Karakatsanis, Konstantinos; Mertzimekis, Theo J.; Koseoglou, Pavlos (HNPS Advances in Nuclear Physics, 2026)
In this work a collective Hamiltonian based on relativistic energy density functional calculations has been used to study the basic spectroscopic properties of Er and Yb isotopes with 82 < 𝑁 < 114. Starting from a series of shape constrained calculations, we build a Bohr-type Hamiltonian the diagonalisation of which gives the collective excitations and transition probabilities. We are thus able to follow the transition of shapes, which is established through projected energy surfaces and specific spectroscopic quantities such as energy ratios and the structure of the low lying excited states.